Analisis Persepsi Kebergunaan, Persepsi Kemudahan, dan Self-Service Technology pada Aplikasi Berbasis Mobile untuk Mahasiswa di Universitas - Christian Christian; Celinka Eira Jove; Livanty Efatania Dendy; Kartika Gianina Tileng (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
In the digital era which continues to develop rapidly, information technology has helped many people's daily activities. This digital transformation includes the implementation of various mobile applications specifically designed to facilitate the teaching and learning process and help students achieve their academic goals. This student mobile application offers a variety of features that can increase efficiency, productivity and student learning experience. Therefore, this research is conducted to understand the acceptance and usage of mobile applications by students using the Technology Acceptance Model (TAM). Technology Acceptance Model (TAM) aims to explain and estimate user acceptance of an information system. Technology Acceptance Model (TAM) provides a theoretical basis for knowing the factors that influence the acceptance of a technology in an organization. In this research, we take 102 people as respondents. We use Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Self-Service Technology (SST), as the independent variables and Actual Use (AU) as a dependent variable. We run multilinear regression and gain the result: Actual Use (AU) = 1.297 + 0.298PU + 0.415PEOU + 0.019SST. It can be seen that the Perceived Usefulness (PU) and Perceived Ease of Use (PEOU) variables have a significant positive effect on the Actual Use (AU) variable, while it is also seen that the Self-Service Technology (SST) variable does not have a significant positive effect on the Actual Use (AU) variable but instead has a negative effect on the Actual Use (AU) variable.